2016
DOI: 10.3945/jn.116.236398
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Alkylresorcinols Reflect Gluten Intake and Distinguish between Gluten-Rich and Gluten-Poor Diets in a Population at Risk of Metabolic Syndrome

Abstract: We propose the use of plasma alkylresorcinols to monitor compliance to a gluten-free diet as well as to help investigations into the possible effects of gluten in the wider population. This trial was registered at www.clinicaltrials.gov as NCT017119913 and NCT01731366.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…A number of studies have demonstrated the strong association between plasma alkylresorcinols and alkylresorcinol intake in a variety of populations, and the overwhelmingly main source of alkylresorcinols in the diet is from the gluten‐containing cereals wheat and rye, with minor contributions from barley and quinoa . We have also found that plasma alkylresorcinols are moderately correlated with self‐reported gluten intake in an intervention setting . Thus, although there was no measurement of gluten intake in the study population, the alkylresorcinol measurements serve as a good proxy for intake of gluten‐containing cereals.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A number of studies have demonstrated the strong association between plasma alkylresorcinols and alkylresorcinol intake in a variety of populations, and the overwhelmingly main source of alkylresorcinols in the diet is from the gluten‐containing cereals wheat and rye, with minor contributions from barley and quinoa . We have also found that plasma alkylresorcinols are moderately correlated with self‐reported gluten intake in an intervention setting . Thus, although there was no measurement of gluten intake in the study population, the alkylresorcinol measurements serve as a good proxy for intake of gluten‐containing cereals.…”
Section: Discussionmentioning
confidence: 79%
“…34 We have also found that plasma alkylresorcinols are moderately correlated with self-reported gluten intake in an intervention setting. 46 Thus, although there was no measurement of gluten intake in the study population, the alkylresorcinol measurements serve as a good proxy for intake of gluten-containing cereals. In the case of healthy controls measured in this study (Figure 1), very low concentrations are just as possible as for people following a gluten-free diet, reflecting that their recent diet has not contained either wheat or rye.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sin duda, es necesario mejorar las capacidades de medir la ingesta de gluten del paciente celíaco a largo plazo. Las mediciones de gluten en heces y/u orina parecen una opción interesante en este aspecto, pero los resultados actualmente disponibles están lejos aún de permitir plantearlas formalmente como una opción de seguimiento en la EC (31)(32)(33)(34)(35) . En este punto es relevante considerar que si hay dudas de si un paciente tiene anticuerpos elevados por que no adhiere a la DLG o porque no responde al tratamiento, una nueva biopsia duodenal sería de utilidad, lo mismo que un estudio genético que muestre ausencia de los haplotipos de riesgo.…”
Section: Discussionunclassified
“…Surveillance of this diet during follow up is difficult because there is no objective way to measure actual gluten ingestion; this is especially so during the transition period of adolescence [4]. None of the existing techniques are completely reliable, including measurements of blood autoantibodies, interviews, questionnaires or the more recently described measurement of 33-mer peptide in feces/urine [5,6] or alkylresorcinols in urine [7], which await validation. At present and both for diagnosis and gluten-free diet control during follow up, measuring blood autoantibodies mainly against transglutaminase 2 (TTG) is the most recommended test worldwide.…”
Section: Introductionmentioning
confidence: 99%